1976
DOI: 10.1002/dev.420090607
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of bioelectric activity in the pre‐ and post‐hatch chick

Abstract: A technique for embryonic implantation and the subsequent recording of electrocortical, neck muscle, and ocular activity continously from the 20th day of incubation through hatching and the first few days thereafter is demonstrated. The embryonic maturation of the EEG, with a characteristic muscle burst pattern heralding hatching was found, supporting previous reports obtained with acute preparations. The technique for injection into the chorioallantoic membrane (CAM) vessels or direct deposition onto the CAM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

1977
1977
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…This is because the depressed muscle tone, presence of eye movements and autonomic instability (including irregular heart and breathing rates), which are all integral to REM sleep (Rattenborg et al 2000), were not measured in most studies. When eye and limb movements were measured (Corner and Bot 1967;Corner et al 1967Corner and Bakhuis 1969;Speciale et al 1976), however, REM or paradoxical sleep, not 'wakefulness', appeared to be the more likely explanation for such EEG epochs. Third, the reports of brief periods of possible 'wakefulness' in chicks which were refolded into glass eggs several hours to days after hatching (Corner et al 1973a;Bakhuis and van de Nes 1979;Bakhuis and Bour 1980) cannot be taken as defi nitive regarding the pre-hatched state, in view of the marked changes in the physiological environment of the chick's brain which are likely to accompany hatching.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This is because the depressed muscle tone, presence of eye movements and autonomic instability (including irregular heart and breathing rates), which are all integral to REM sleep (Rattenborg et al 2000), were not measured in most studies. When eye and limb movements were measured (Corner and Bot 1967;Corner et al 1967Corner and Bakhuis 1969;Speciale et al 1976), however, REM or paradoxical sleep, not 'wakefulness', appeared to be the more likely explanation for such EEG epochs. Third, the reports of brief periods of possible 'wakefulness' in chicks which were refolded into glass eggs several hours to days after hatching (Corner et al 1973a;Bakhuis and van de Nes 1979;Bakhuis and Bour 1980) cannot be taken as defi nitive regarding the pre-hatched state, in view of the marked changes in the physiological environment of the chick's brain which are likely to accompany hatching.…”
Section: Discussionmentioning
confidence: 95%
“…First, the evidence shows that sleep-like states predominate (Peters et al 1965;Ookawa 1972;Corner et al 1973a;Speciale et al 1976;Bakhuis and van de Nes 1979;Bakhuis and Bour 1980). Second, the short periods of pre-hatching EEG activity described by some as 'wakefulness' (Ookawa 1972;Corner et al 1973a;Bakhuis and van de Nes 1979;Bakhuis and Bour 1980) in fact could not be distinguished from similar EEG patterns that are present during REM sleep.…”
Section: Discussionmentioning
confidence: 95%
“…While REM sleep can be first identified 1 – 2 d before chicken embryos hatch [38,39], age-related changes in REM sleep have been examined primarily following hatching. Several studies have reported that REM sleep as a % of total sleep time (%REM sleep) declines with age from higher amounts occurring shortly (0 – 8 h) after hatching [30,31,40,41]. However, others have reported lower %REM sleep in newly hatched chicks [33].…”
Section: Discussionmentioning
confidence: 99%
“…Research efforts have largely concerned the use of the EEG either as an indicator of the general integrity of the nervous system (Corner & Bakhuis, 1969;Muller & Scheich, 1986) or as a measure of specific brain states such as sleep cycles and other EEG rhythm defined states (Corner, Bakhuis, & van Wingerden, 1973;Ookawa & Gotoh, 1965;Ookawa & Takagi, 1968;Speciale, Correspondence to: M. Hunter Contract grant sponsor: University of Newcastle Contract grant number: RMC 280-1086 Nawaczyk, & Jouvet, 1976). Of those studies using the EEG as a measure of the functional integrity of the chicken nervous system, a major interest has been to plot the embryonic development of the chicken brain.…”
mentioning
confidence: 99%